An Evaluation of a Marginal Land’s Geological Engineering Properties in Borikiri Sandfill, Port Harcourt Nigeria - Tammy Morrison; Erefama Ekine Esonanjor (Archives of Current Research International, 2023)
Aim: The aim of this study was to assess the geological engineering properties of a marginal land in Borikiri Sandfill, Port Harcourt, Nigeria, using both field and laboratory investigations. Study Design: The study design involved the drilling of 4 boreholes and standard penetration tests to determine the soil profile and index properties such as particle size analysis, atterberg limits, and moisture content. Consolidation and triaxial tests were also performed to determine the values of the coefficients of permeability (k), volume compressibility (Mv), and consolidation (Cv). Place and Duration of Study: The Study was conducted in Borikiri Sandfill, Port Harcourt between February and May 2020. Methods: This study's methodology included field research, laboratory analysis, and testing. Drilling and conventional penetration tests were used to assess the soil profile. Laboratory tests such as particle size analysis, atterberg limits, and moisture content were used to determine the index characteristics. The values of permeability (k), volume compressibility (Mv), and consolidation (Cv) were also determined using triaxial and consolidation tests. Results: The results of the study showed that the soil profile consists of five stratigraphic sequences, with a top organic silty layer followed by a sandy layer, a dark plastic layer, a dark silty clayey sand, and a well-graded sand. The clays had an average Liquid limit (LL) of 45% and a Plastic Limit (PL) value of 23%. The values of k, Mv, and Cv were determined to be 2.1 x 10-7 m/s, 1.8 x 10-4–2.5 x 10-4 m2/MN, and 3.8 m2/yr, respectively. The average bearing capacity values at 2.5 m and 4.5 m depths were determined to be 186.39 kPa and 278.71 kPa, respectively. Settlement values were calculated empirically for immediate and consolidation settlement, with immediate settlement being high at 25.85 mm and consolidated settlement being 7.53mm. T50 and T90 values were also determined to be 1.32 and 4.52 years, respectively. Conclusion: It is recommended that a shallow foundation, down to the first layer, can be used for any light construction on the marginal land in Borikiri Sandfill, Port Harcourt, Nigeria. The values of k, Mv, and Cv also indicate that the soil is relatively compressible, which should be taken into account in any design or construction activities.